A prospective multicenter phase II study of intrabone marrow transplantation of unwashed cord blood using reduced‐intensity conditioning. (17th January 2018) - Okada, Masaya; Tasaka, Taizo; Ikegame, Kazuhiro; Aotsuka, Nobuyuki; Kobayashi, Takeshi; Najima, Yuho; Matsuhashi, Yoshiko; Wada, Hideho; Tokunaga, Hirotoshi; Masuda, Shinichi; Utsu, Yoshikazu; Yoshihara, Satoshi; et al.
Abstract: Cord blood transplantation (CBT) is associated with delayed hematopoietic recovery and graft failure. To overcome these problems, we conducted a prospective, multicenter phase II study of intrabone marrow transplantation in which patients received reduced‐intensity conditioning without anti‐thymocyte globulin (ATG). The primary endpoint was the probability of full donor engraftment. Forty patients with hematologic malignancies were enrolled. Cord blood (CB) cells were injected without washing into 4 iliac bone sites (2 at each hemipelvis), at which approximately 6 mL of CB was administered at one site with local anesthesia. Full donor engraftment rate was 86.8%. The cumulative incidence of neutrophil and platelet engraftment was 86.4% and 85.5%, respectively. The median time to neutrophil (>0.5 × 10 9 /L) and platelet (2.0 × 10 9 /L) recovery was 17.5 and 44 days, respectively. The probability of severe acute graft‐vs‐host disease (GVHD) was 47.5%. The cumulative incidence of extensive chronic GVHD was 3.0%. The probability of relapse and non‐relapse mortality was 30.4% and 28.0%, respectively. The survival rate at 3 years was 45.6%, although most patients were at an advanced stage. These results suggest that our intrabone marrow‐CBT procedure without using ATG improves hematopoietic recovery and decreases the incidence of chronic GVHD, but does not decrease the incidence of acute GVHD.